Karyotype Description of Two Andean Species of the guarani Group of Drosophila (Díptera: Drosophilidae) and Cytological Notes. Issue 3 (15th May 2021) - Vela, Doris; Villavicencio, Erika
Abstract: The guarani group of Drosophila genus (Diptera: Drosophilidae) is formed by 24 species however the relationship of these species is not clear. In the present study are described the karyotypes of Drosophila sachapuyu Peñafiel and Rafael, 2018 and Drosophila zamorana Peñafiel and Rafael, 2018, two Andean species members of the guarani group. Mitotic chromosomes from cerebral ganglia of third stand larval were obtained by thermal shock and cell suspension techniques. The karyotype of D. sachapuyu, presents 2n = 10 (4R, 1V; X = R, Y = R) while D. zamorana exhibits karyotype 2n = 12 (5R, 1V; X = V, Y = R).